1999
DOI: 10.1016/s0735-1097(99)00318-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibition reduces monocyte chemoattractant protein-1 and tissue factor levels in patients with myocardial infarction

Abstract: This study demonstrated that administration of enalapril reduces the increased procoagulant activity in patients with myocardial infarction associated with inhibition of the activation and accumulation of macrophages and monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 43 publications
3
40
0
2
Order By: Relevance
“…Therefore, it is necessary to consider the MI models used in different studies. Consistent with the results of the experimental studies, elevated serum concentrations of several chemokines were observed in patients with MI, 33 suggesting the clinical significance of chemokines in the pathophysiology of MI.…”
Section: Takahashi Msupporting
confidence: 85%
“…Therefore, it is necessary to consider the MI models used in different studies. Consistent with the results of the experimental studies, elevated serum concentrations of several chemokines were observed in patients with MI, 33 suggesting the clinical significance of chemokines in the pathophysiology of MI.…”
Section: Takahashi Msupporting
confidence: 85%
“…48 Of particular interest is the observation that angiotensin II induces TF expression in monocytes, endothelial cells, and vascular smooth muscle cells 24,32 through the angiotensin II type I receptor (AT-I). 32 Consistently, both ACE inhibitors 49 and AT-I receptor blockers 50 reduce TF plasma activity in hypertensive patients. ACE inhibitors also reduce endotoxin-induced TF expression in monocytes, 51 suggesting a pleiotropic effect of this class of drugs.…”
Section: Cardiovascular Risk Factorsmentioning
confidence: 79%
“…23,[33][34][35][36] In addition to lowering cholesterol levels, life-saving statin therapy attenuates the production of inflammatory cytokines and coagulant factors and decreases the expression of cell adhesion molecules by circulating monocytes in hypercholesterolemic patients. [37][38][39] Angiotensin-converting enzyme inhibitors reduce tissue factor and serum levels of monocyte chemotactic protein 1 in patients after acute MI, 40 decelerating the coagulationinflammation-thrombosis cascade. Furthermore, addition of the renin inhibitor aliskiren suppresses circulating numbers of classical monocytes and increases myocardial salvage after acute MI.…”
mentioning
confidence: 99%